2019
DOI: 10.1111/eci.13122
|View full text |Cite
|
Sign up to set email alerts
|

Synchronized expressions of serum osteopontin and B cell–activating factor in autoimmune thyroid disease

Abstract: Background Osteopontin (OPN) is recognized as a potent immunoregulator of autoimmune disease. In the study, we tried to explore the association of serum OPN levels with autoimmune thyroid disease, including Graves' disease (GD) and Hashimoto's thyroiditis (HT), in an ethnic Chinese population. Materials and methods We enrolled 131 patients with GD, 33 patients with HT and 123 healthy controls. Serum OPN, B cell–activating factor (BAFF) and interferon (IFN)‐α levels were quantified. Graves' disease patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 41 publications
(91 reference statements)
1
4
0
Order By: Relevance
“…We recruited 84 patients with GD and 27 healthy donors (general clinical characteristics are summarized in Table 1 and Figure 1A) to evaluate BAFF expression. The results showed that the serum BAFF levels were significantly higher in GD patients than in healthy donors (Figure 1B), which is consistent with results reported in previous studies (14, 15, 22). To determine the factors related to BAFF overexpression, serum FT3, FT4, TRAb, TGAb, and TPOAb levels were measured, and the relationship between these data and BAFF was evaluated.…”
Section: Resultssupporting
confidence: 92%
“…We recruited 84 patients with GD and 27 healthy donors (general clinical characteristics are summarized in Table 1 and Figure 1A) to evaluate BAFF expression. The results showed that the serum BAFF levels were significantly higher in GD patients than in healthy donors (Figure 1B), which is consistent with results reported in previous studies (14, 15, 22). To determine the factors related to BAFF overexpression, serum FT3, FT4, TRAb, TGAb, and TPOAb levels were measured, and the relationship between these data and BAFF was evaluated.…”
Section: Resultssupporting
confidence: 92%
“…However, the association between thyroiditis and OPN is controversial. Cheng et al found no significant difference in OPN levels between inactive HT and normal controls and between active HT and controls, but they found higher serum OPN levels in active than in inactive Graves' disease and controls (Cheng et al, 2019). Due to this controversy, we excluded patients with thyroiditis findings in ultrasonographic evaluation from the study.…”
Section: Discussionmentioning
confidence: 96%
“…Either imbalanced BAFF or OPN can escape immune tolerance and result in AID development [ 45 50 ]. Moreover, in our recent publications, we demonstrated that serum BAFF and OPN levels were upregulated in GD, were associated with TSHRAb and thyroid function, and suggested that both BAFF and OPN could exhibit remarkable roles in inducing GD and modulating disease progression [ 51 , 52 ]. Correlations of KRT1 with BAFF and OPN levels indicate that the existence of KRT1 with either BAFF or OPN might be coordinated.…”
Section: Discussionmentioning
confidence: 99%